Myocardial Damage in SARS-CoV-2 Infection - Elizabeth Sellén Sanchén; Joaquín Sellén Crombet; Lisandra Sellén Fundora (Universidad de las Ciencias Médicas de Cienfuegos, 2020)
Cardiovascular manifestations induced by the new coronavirus SARS-CoV-2 may give a fatal course to COVID-19 and cause alarm in the world medical community. Patients with a history of arterial hypertension, coronary heart disease and cardiomyopathy constitute a very high risk population of complications from the coronavirus. Therapeutic behavior must be prioritized and intensive. The current world epidemiological situation requiere an active medical behavior in patients with cardiovascular disease and COVID-19 given their predisposition to develop myocardial damage and death. A search was carried out in the medical literature of recent years about the coronavirus and its implications in the cardiovascular system, specifically myocardial damage. The objective of this research is to demonstrate through the review of recent research how the myocardial damage produced by the virus justifies the high mortality of this pandemic.